2015
DOI: 10.1007/s11010-015-2326-1
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training improves oxidative stress and ubiquitin proteasome system activity in heart of spontaneously hypertensive rats

Abstract: The activity of the ubiquitin proteasome system (UPS) and the level of oxidative stress contribute to the transition from compensated cardiac hypertrophy to heart failure in hypertension. Moreover, aerobic exercise training (AET) is an important therapy for the treatment of hypertension, but its effects on the UPS are not completely known. The aim of this study was to evaluate the effect of AET on UPS's activity and oxidative stress level in heart of spontaneously hypertensive rats (SHR). A total of 53 Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…In fact, we [ 5 ] and others [ 4 ] observed cardiac UPS hypoactivation in animals with ischemia-induced CHF. Importantly, severe CHF is also associated with UPS hypoactivation [ 3 , 4 , 29 ] while UPS overactivation is mostly observed in models of compensated cardiac hypertrophy [ 28 , 30 ]. Therefore, our findings suggest that α 2A /α 2C ARKO mice at seven months of age may still be able to degrade modified proteins at the expense of the overactivation of UPS.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we [ 5 ] and others [ 4 ] observed cardiac UPS hypoactivation in animals with ischemia-induced CHF. Importantly, severe CHF is also associated with UPS hypoactivation [ 3 , 4 , 29 ] while UPS overactivation is mostly observed in models of compensated cardiac hypertrophy [ 28 , 30 ]. Therefore, our findings suggest that α 2A /α 2C ARKO mice at seven months of age may still be able to degrade modified proteins at the expense of the overactivation of UPS.…”
Section: Discussionmentioning
confidence: 99%
“…This is a sensitive and accurate method, with good stability to light/oxygen and with high reproducibility (Gay & Gebicki, ; Mehta, Darji, & Aparnathi, ; Orefice et al., ; Yu, Wang, Zhou, Zhao, & Qiu, ). The FOX method can be employed for determining H 2 O 2 (Nourooz‐Zadeh, ; Sturza et al., ; Yu et al., ), lipid (Ceylan et al., ; Gay & Gebicki, ; Nourooz‐Zadeh, ; Venturini, Simao, & Dichi, ), and protein (Gay & Gebicki, ) hydroperoxides in a wide range of biological samples, from serum (Takci et al., ) and lipoproteins (Erel, ) to cerebrospinal fluid, urine (Erel, ), and tissue homogenates (de Andrade et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These meta-analyses showed that aerobic exercise training is associated with modest improvements in cognitive function such as attention, processing speed, executive function and memory. Based on studies using animal models and human subjects, several hypotheses have been proposed to describe the mechanisms behind the beneficial effects of exercise on cognition; these include a reduction in oxidative stress [6] , an increase in growth factor levels (e.g., brain-derived neurotrophic factor, insulin-like growth factor, and vascular endothelial growth factor) [7] , [8] , [9] , [10] , and reduced levels of amyloid-β (Aβ), a key pathogenic factor in Alzheimer's disease (AD) [11] .…”
Section: Introductionmentioning
confidence: 99%